Health status, healthcare utilisation, and quality of life among the coastal communities in Sabah Protocol of a population-based survey - Dahlui, Maznah; Azzeri, Amirah; Zain, Mohd Aizat; Noor, Mohd Iqbal Mohd; Jaafar, Hafiz; Then, Amy Yee Hui; Suhaimi, Julia; Kari, Fatimah; Creencia, Lota A.; Madarcos, John Roderick; Jose, Edgar; Fleming, Lora E.; et al. (Lippincott Williams & Wilkins, 2024)
Indexed by WOS